Psychoeducation: Issues and Directions for Research - N. D. Semenova; A. Yu. Kuzmenko; G. P. Kostyuk (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2018)
Psychoeducational interventions for schizophrenic patients and their families have shown impressive long-term effects on the course of illness. The authors conducted a review of scholarly journals and manuscripts indexed in commonly used search engines. The psychoeducation varied in approach and format: family psychoeducation, individual- and group-based interventions, flexible combined approaches, interventions to improve medication adherence etc. This paper points to a growing interest in the topic of psychoeducation for schizophrenic patients, providing a comprehensive picture of group-based interventions and highlighting the need for additional research and knowledge-building.